2016
DOI: 10.1139/cjps-2015-0242
|View full text |Cite
|
Sign up to set email alerts
|

Asparagus cultivars with varying adaptation to southern Ontario differ for induction of freezing tolerance in the fall

Abstract: Asparagus (Asparagus officinalis L.) cultivars differ for adaptation in southern Ontario, and delayed or decreased acquisition of freezing tolerance in the fall could explain, in part, the diminished longevity observed in some germplasm. A field study was conducted to determine the relationship between LT 50 , the lethal temperature at which 50% of plants die, and physiological parameters related to freezing tolerance, in three cultivars with varying adaptation in southern Ontario: Guelph Millennium (GM) > Jer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
1
7
1
Order By: Relevance
“…The ranking of LT 50 values for three cultivars at the end of the spring sampling period in both years, GM<JG<UC, is consistent with observations from cold acclimation of seedlings in controlled environments (Kim and Wolyn, 2015;Landry and Wolyn, 2012) and early fall acclimation of crowns in the field (Panjtandoust and Wolyn, 2016). Thus, fall and spring freezing tolerance is correlated in these three genotypes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The ranking of LT 50 values for three cultivars at the end of the spring sampling period in both years, GM<JG<UC, is consistent with observations from cold acclimation of seedlings in controlled environments (Kim and Wolyn, 2015;Landry and Wolyn, 2012) and early fall acclimation of crowns in the field (Panjtandoust and Wolyn, 2016). Thus, fall and spring freezing tolerance is correlated in these three genotypes.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, fall and spring freezing tolerance is correlated in these three genotypes. Cultivars differed for LT 50 values at early fall samplings with values for GM lower than those for UC; however, they did not differ in late fall (Panjtandoust and Wolyn, 2016). Conversely, the two cultivars did not differ for the early spring sampling dates but did differ at the final sampling dates in this study.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…A series of physiological, biochemical, and molecular changes induced by photoperiod and temperature maximize the freezing tolerance of plants during acclimation 3 5 . Earlier research indicated that the hardiness of perennial ryegrass ( Lolium perenne L.) 6 and asparagus ( Asparagus officinalis L.) 7 , 8 is negatively associated with increasing water contents. A decrease in the water content can lower the freezing point of cells, whereas an increase in the water content may result in mechanical damages due to extracellular freezing as well as an increase in the ice propagation rate in tissues 7 9 .…”
Section: Introductionmentioning
confidence: 99%